Managing R&D for competitive advantage - Menke, Michael M.
Michael M. Menke demonstrates how "best practices" for making R&D decisions can be used to gain competitive advantage.
Difficult to learn, hard to do well and expensive to implement, these ten 'best practices' can confer competitive advantage on those organizations able to implement them.
A benchmarking study of 79 highly-regarded R&D organizations has revealed ten practices for making excellent R&D decisions and ten additional practices most likely to confer competitive advantage on those organizations that learn to master them. Although these leading organizations acknowledge such "best practices" as "learn from post-project audits" and "anticipate competition" to be very important, only a few companies within this select group have been able to master them. The best practices database is thus proving to be a useful resource for companies that wish to diagnose their R&D strategic excellence and then to take appropriate improvement steps.
Keywords: R&D.